Exploring Cathode Materials for Sodium Ion Rechargeable Batteries - Kamaluddin Khan (International Journal of Advanced Science and Technology, 2020)
The demand for green energy technologies have intensified the pursuit of high-performance and cost-effective battery systems. Li ion batteries offer the highest energy density among present battery technologies but there are many hindrances such as Li sources availability, cost, and safety. Alternative rechargeable battery systems with transporting ions other than Li ion have attracted growing interests in recent years. Sodium is a cheap, nontoxic and abundant element that is uniformly distributed around the world and therefore is considered ideal for transporting ion in alternative rechargeable batteries. The breakthrough or the advances in these batteries mainly depends on the type of cathode material used. Most studies show that, doping the cathode material leads to an increase in cell voltage, lower activation energy and higher diffusion coefficient. Intercalating the compounds of Sodium with transitional metals leads to higher cycling capability and high capacity. Simulations play a pivotal role in providing a better insight into the crystal structure and electrochemical behaviour of the newly synthesized electrode material. Layered transition metal oxides and polyanionic compounds are dominating the class of cathode materials due to their attractive properties such as high storage capacity and fast charge storage ability. Sodium ion battery materials continue to grow at a fast pace. Superior quality cathode materials can be synthesized by mastering resource availability, crystalline structure and elemental compositions.